1993
DOI: 10.1002/ccd.1810280310
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic recognition of a proximal balloon tear during inoue balloon mitral valvotomy

Abstract: Two patients in whom a proximal balloon tear accompanied by a unique angiographic appearance occurred during percutaneous balloon mitral valvotomy using the Inoue balloon catheter are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Chow et al reported two cases of proximal balloon tear during PTMC by Inoue balloon and they attributed to the suboptimal quality of rubber layer might be responsible. [6] Schilling et al reported two cases of balloon tear occurring in the proximal portion of the Inoue balloon. [7] They reported that the rupture was associated with calcify valves.…”
Section: Discussionmentioning
confidence: 99%
“…Chow et al reported two cases of proximal balloon tear during PTMC by Inoue balloon and they attributed to the suboptimal quality of rubber layer might be responsible. [6] Schilling et al reported two cases of balloon tear occurring in the proximal portion of the Inoue balloon. [7] They reported that the rupture was associated with calcify valves.…”
Section: Discussionmentioning
confidence: 99%
“…Chow et al also reported two cases in which the proximal portion of the balloon tore but did not say whether the valves were calcified. 7 Though the three layer wall of the Inoue balloon may be apt to tear, it prevents release of the balloon contents into the circulation, whereas cylindrical polyethylene balloons do not.8…”
mentioning
confidence: 99%